Hydrocortisone normalizes oxygenation and cGMP regulation in lambs with persistent pulmonary hypertension of the newborn - Perez, Marta (American Physiological Society, 2012)
In the pulmonary vasculature, cGMP levels are regulated by soluble guanylate cyclase (sGC) and phosphodiesterase 5 (PDE5). We previously reported that lambs with persistent pulmonary hypertension of the newborn (PPHN) demonstrate increased reactive oxygen species (ROS) and altered sGC and PDE5 activity, with resultant decreased cGMP. The objective of this study was to evaluate the effects of hydrocortisone on pulmonary vascular function, ROS, and cGMP in the ovine ductal ligation model of PPHN. PPHN lambs were ventilated with 100% O(2) for 24 h. Six lambs received 5 mg/kg hydrocortisone every 8 h times three doses (PPHN-hiHC), five lambs received 3 mg/kg hydrocortisone followed by 1 mg·kg(−1)·dose(−1) times two doses (PPHN-loHC), and six lambs were ventilated with O(2) alone (PPHN). All groups were compared with healthy 1-day spontaneously breathing lambs (1DSB). O(2) ventilation of PPHN lambs decreased sGC activity, increased PDE5 activity, and increased ROS vs. 1DSB lambs. Both hydrocortisone doses significantly improved arterial-to-alveolar ratios relative to PPHN lambs, decreased PDE5 activity, and increased cGMP relative to PPHN lambs. High-dose hydrocortisone also increased sGC activity, decreased PDE5 expression, decreased ROS, and increased total vascular SOD activity vs. PPHN lambs. These data suggest that hydrocortisone treatment in clinically relevant doses improves oxygenation and decreases hyperoxia-induced changes in sGC and PDE5 activity, increasing cGMP levels. Hydrocortisone reduces ROS levels in part by increasing SOD activity in PPHN lambs ventilated with 100% O(2.) We speculate that hydrocortisone increases cGMP by direct effects on sGC and PDE5 expression and by attenuating abnormalities induced by oxidant stress.